Additional morphometrical data on some Heligmonellidae (Nematoda: Trichostrongylina) parasitic in Neotropical rodents (Cricetidae) - Durette Desset, M. C. (2010)
Some additional morphological and metrical data are provided, particularly on the synlophe of the following species: Hassalstrongylus dessetae Pinto, 1978, Stilestrongylus eta (Travassos, 1937), Stilestrongylus manni Denké & Murúa, 1977 and Stilestrongylus valdivianus Durette-Desset & Murúa, 1979, based on type and voucher material deposited in Brazilian and French collections. Heligmonoides crassidorsualis Franco, 1967 is considered as a Nippostrongylinae incertae sedis: its synlophe not being known it is impossible to report the species to a given genus. However, it is unlikely that the species belong to the genus Heligmonoides Baylis, 1928, present only in commensal Murinae from the Old World. Heligmonoides mirzai Smales, 2009, is also regarded, temporarily, as a Nippostrongylinae incertae sedis.